The literary heritage of V.O. Gogol-Yanovsky in the context of his era’s culture - Ніколенко, Ольга Миколаївна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
The article explores the previously unknown facts of Vasyl Opanasovych Gogol-Yanovsky’s life and creative work, based on his contemporaries’ memoirs, Mykola Gogol’s letters, and different biographers’ studies. Moreover, the article reveals the crucial meaning of V.O. Gogol-Yanovsky’s works for the development of new trends in Ukrainian and Russian literatures in the 18th and 19th centuries. As for his dramatic works, the article studies the central topics and motives thereof, as well as their connection to Ukrainian vertep and the Age of Enlightenment in Europe. V.O. Gogol-Yanovsky’s influence on Mykola Gogol’s poetic conscience is well grounded, especially in terms of structural peculiarities in “Evenings on a Farm near Dykanka” by M. Gogol. The article provides a detailed analysis of a play by V.O. Gogol-Yanovsky entitled “A Flathead, or a Woman’s Finesse, Outwitted by a Soldier”, which had been proofread by Panteleymon Kulish. Comedies and vaudevilles by V.O. Gogol-Yanovsky are compared to plays by I. Kotlyarevsky (“Natalka from Poltava” and “The Muscovite-Sorcerer”). The article proves the relevance of V.O. Gogol-Yanovsky’s creative work for the development of drama in the 18th and 19th centuries, as well as for the development of Ukrainian literary language.